2021
DOI: 10.1007/s13157-021-01449-y
|View full text |Cite
|
Sign up to set email alerts
|

Wetland Conservation: Challenges Related to Water Law and Farm Policy

Abstract: Water is essential for wetland function and sustaining migratory networks for wetland wildlife across broad landscapes. Groundwater declines and surface flow reductions that impact aquatic and wetland organisms are common in the western U.S. and increasingly in the eastern U.S. Agriculture is the largest consumptive water use in the U.S. and understanding economic incentives of water-use practices and the legal context of water rights is foundational to identifying meaningful water solutions that benefit all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…Human population growth and climate change are placing unprecedented pressure on limited water resources (Dawadi & Ahmad, 2012; Hansen et al., 2002). As wetlands are increasingly converted to agriculture, wetlands created or maintained by flood irrigation of agricultural water resources are now the most widely available mesic area for wildlife (Donnelly et al., 2020; King et al., 2021). Given the important and complex relationship between sensitive species, such as sage‐grouse, and the availability of large mesic areas, it will be increasingly important for water availability to be managed while considering the needs of both people and wildlife, and the value of vegetation structure and edge habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Human population growth and climate change are placing unprecedented pressure on limited water resources (Dawadi & Ahmad, 2012; Hansen et al., 2002). As wetlands are increasingly converted to agriculture, wetlands created or maintained by flood irrigation of agricultural water resources are now the most widely available mesic area for wildlife (Donnelly et al., 2020; King et al., 2021). Given the important and complex relationship between sensitive species, such as sage‐grouse, and the availability of large mesic areas, it will be increasingly important for water availability to be managed while considering the needs of both people and wildlife, and the value of vegetation structure and edge habitats.…”
Section: Discussionmentioning
confidence: 99%
“…Watersheds define landscape boundaries in geologically and ecologically meaningful ways, and can be used to demonstrate how neighboring land users are linked by processes affecting water supply and quality (King et al 2021).…”
Section: Freshwater Priorities For Evaluating Existing and Proposed P...mentioning
confidence: 99%
“…However, even with the protection of these areas by Brazilian law, we found that more than 40% of the total Veredas area is currently used for farming. The indiscriminate use of wetlands is an international issue (King et al 2021), and in Brazil it can be explained by the stimulus to commodities production since the 1970s (Pereira 2012). In addition to the agricultural expansion, during the military dictatorship, the Brazilian government promoted the use of wetlands, including Veredas, in a disastrous program "Provárzeas Nacional" (Brazil 1981), which was supported by farmers and even by a few researchers (Reis and Rassini 1985).…”
Section: Veredas Land Covermentioning
confidence: 99%